2012
DOI: 10.1021/jo300594b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antisense Properties of Fluoro Cyclohexenyl Nucleic Acid (F-CeNA), a Nuclease Stable Mimic of 2′-Fluoro RNA

Abstract: We report the design and synthesis of 2′-fluoro cyclohexenyl nucleic acid (F-CeNA) pyrimidine phosphoramidites and the synthesis and biophysical, structural, and biological evaluation of modified oligonucleotides. The synthesis of the nucleoside phosphoramidites was accomplished in multigram quantities starting from commercially available methyl-D-mannose pyranoside. Installation of the fluorine atom was accomplished using nonafluorobutanesulfonyl fluoride, and the cyclohexenyl ring system was assembled by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 57 publications
0
53
0
Order By: Relevance
“…FHNA, 23 F-CeNA, 24 N-MC, 37 and F-N-MC 36 phosphoramidites were synthesized as described in the literature. ASOs were synthesized on an ABI 394 DNA/RNA Synthesizer on a 2 μmol scale using 5-methyl cytidine MOE-loaded primer support (215 μmol/g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FHNA, 23 F-CeNA, 24 N-MC, 37 and F-N-MC 36 phosphoramidites were synthesized as described in the literature. ASOs were synthesized on an ABI 394 DNA/RNA Synthesizer on a 2 μmol scale using 5-methyl cytidine MOE-loaded primer support (215 μmol/g).…”
Section: Methodsmentioning
confidence: 99%
“…However, the six-membered hexitol ring in FHNA is more rigid and mimics the RNA-like C3′- endo conformation of the furanose ring (Figures 1B and 1C) 23 . In contrast, the cyclohexenyl ring in F-CeNA is more flexible and was shown to assume either the DNA- or RNA-like sugar conformation depending on the sequence context on its incorporation 24 . The 3.1.0 ring system in F-NMC is locked in the RNA-like C3′- endo conformation 25 .…”
Section: Introductionmentioning
confidence: 98%
“…[3] We recently characterized the antisense properties of both isomers of 2'-fluorohexitol nucleic acid (FHNA) [4,5] and 2'-fluorocyclohexenyl nucleic acid (F-CeNA). [6] We found that fluorine incorporation can indeed have a beneficial effect on the properties of modified oligonucleotides as compared to those of the parent nonfluorinated counterparts. As a continuation of that program and our interest in the synthesis of carbocyclic nucleoside analogues, [7] we investigated the synthesis and duplexstabilizing properties of both isomers of 2'-F-modified Nmethanocarbathymidine (N-MCT) oligonucleotides.…”
Section: Introductionmentioning
confidence: 73%
“…Copies of 1 H-, 13 C-, 19 F-, and 31 P-NMR spectra of compounds 2−18 and X-ray structural data (CIF) of compound 16. This information is available free of charge via the Internet at http://pubs.acs.org…”
Section: Supporting Informationmentioning
confidence: 99%